Pengaruh Konflik Dan Stres Kerja Terhadap Kinerja Karyawan Pada PT. Telkom Wilayah Telekomunikasi (WITEL) Medan - Mahdiyyah, Nurul; Syafrizal, Syafrizal; Julkarnain, Julkarnain (Universitas Islam Islam Sumatera Utara, 2023)
This research is limited to Conflict and Work Stress, especially regarding the work targets implemented and also Work Stress given by PT. Telkom Witel Medan has not been able to improve Employee Performance. The formulation of the problem in this research is what is the influence of Conflict and Work Stress on Employee Permormance at PT. Telkom Witel Medan. The pupose of this research is to determine the effect of Conflict and Work Stress on Employee Performance at PT. Telkom Witel Medan. The population in this study was 40 employees. This research approach is a quantitative approach. The testing method uses SPSS. Based on the test results and analysis, it shows that there is a positive and significant influence of Conflict and Work Stress variables on Employee Performance variables.